2020
DOI: 10.1364/ao.391736
|View full text |Cite
|
Sign up to set email alerts
|

Digital all-sky polarization imaging of the total solar eclipse on 21 August 2017 in Rexburg, Idaho, USA

Abstract: All-sky polarization images were measured from sunrise to sunset and during a cloud-free totality on 21 August 2017 in Rexburg, Idaho using two digital three-camera all-sky polarimeters and a time-sequential liquid-crystal-based all-sky polarimeter. Twenty-five polarimetric images were recorded during totality, revealing a highly dynamic evolution of the distribution of skylight polarization, with the degree of linear polarization becoming nearly zenith-symmetric by the end of totality. The surrounding environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…The maximum value of DoLP identically equals 1 in the Rayleigh single scattering model, but the actual DoLP in the celestial dome scarcely reaches 1 because of the multiple scattering effects [92]. Moreover, the existence of four neutral points where the emitted light is unpolarized (DoLP equals 0) has been verified and studied widely [70,[95][96][97], but it cannot be correctly described under the framework of the Rayleigh scattering theory. To model depolarization phenomena, Berry et al [98] proposed a singular value model to describe the existence of neutral points, and Hannay [99] presented a model to characterize the multiple scattering.…”
Section: Atmospheric Polarized Light Field Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum value of DoLP identically equals 1 in the Rayleigh single scattering model, but the actual DoLP in the celestial dome scarcely reaches 1 because of the multiple scattering effects [92]. Moreover, the existence of four neutral points where the emitted light is unpolarized (DoLP equals 0) has been verified and studied widely [70,[95][96][97], but it cannot be correctly described under the framework of the Rayleigh scattering theory. To model depolarization phenomena, Berry et al [98] proposed a singular value model to describe the existence of neutral points, and Hannay [99] presented a model to characterize the multiple scattering.…”
Section: Atmospheric Polarized Light Field Modelingmentioning
confidence: 99%
“…Jensen et al [195] established a physical model of the night skylight and analyzed the main components of the skylight as well as the influence of different light sources on the night imaging effect. In addition, the atmospheric polarization patterns during eclipses were also studied [97,183,196]. The mechanism of the navigation of aquatic animals using polarized skylight was also being researched [11,52].…”
Section: Atmospheric and Weather Conditionsmentioning
confidence: 99%
“…During the recent total eclipse on 21 August 2017, Bernhard and Petkov (2019) made surface spectral solar irradiance observations and performed 3D radiative transfer simulations; Ockenfuβ et al (2020) further used 3D radiative transfer simulations for understanding the impact of surface spectral albedo, ozone vertical distribution and surrounding mountains on surface spectral irradiance observed by Bernhard and Petkov (2019); Wen et al (2020) used ground-based pyranometer observations to estimate the impact of solar eclipse on surface broadband irradiance reduction; Calamas et al (2018) studied the impact of the eclipse on surface irradiance and ambient temperature; and Eshelman et al (2020) studied impact of total solar eclipse on all-sky polarization images. Gedzelman (2020) showed that the sunlit tops of cloud layers and arctic sea ice near the umbra appeared salmon-brown when viewed from airplanes or satellite during the 21 August 2017 as well as 2 July 2019 eclipse.…”
Section: Introductionmentioning
confidence: 99%